The Expressive Semantic Skills of Sesotho-Speaking Toddlers (28 and 30 months): A Comparison using the Sesotho Picture-Naming Vocabulary Task and the Preliminary Version of the Sesotho Communicative Development Inventory - Naidoo, Kerchia (University of the Witwatersrand, Johannesburg, 2024)
Background: At present, there exists little to no standardised methods of assessing language- related skills which have been normed within the South African population. This makes it difficult for a Speech-Language Pathologist to accurately diagnose language or communication difficulties within this context, and has resulted in inappropriate interventions and the stigma of disability associated with a child with a language impairment. It is therefore imperative that Speech-Language Pathologists use assessment tools that are fit for purpose, i.e. culturally appropriate and linguistically relevant for the diverse child populations in South Africa. The intention for this research study is to assist the South African Communicative Development Inventory team in addressing the concerns of culturally and contextually inappropriate assessment methods. Aims: The key aim of this research study was to compare the results of a Basotho child’s expressive, semantic language skills using the caregiver-report Communicative Development Inventory and the picture-naming vocabulary task. The objectives were to: (i) describe the contextual background of Sesotho-speaking child participants which may have influenced their communication development; (ii) describe the child participants’ semantic communication abilities using the Sesotho Communicative Development Inventory; and (iii) describe the child participants’ expressive semantic abilities using the picture-naming vocabulary task. Method: This research study employed a mixed methods approach using multiple case studies. The case studies comprised of caregiver-child dyads. Both quantitative and qualitative paradigms were utilised to achieve the mixed methods approach. The non-probability, purposive sampling method assisted in selecting participants for this study. The data collection was conducted in a predominantly monolingual Sesotho-speaking population in Tweeling, Free State. A total sample size of 20 – 10 adult and 10 child participants – was chosen for this study. The adult participants were the adult caregivers of the child participants. The child participants were chosen between 28 and 30 months of age who are monolingual Sesotho speakers. Three data collection instruments were administered on the chosen participants: a family background questionnaire; a Sesotho picture-naming vocabulary task; and the Sesotho Communicative Development Inventory. The analysis of the assessment instruments used descriptive statistics, inferential statistics, and semantic analysis. Results: A significant correlation was found between the Sesotho Communicative Development Inventory and the Sesotho picture-naming vocabulary task. The Communicative Development Inventory highlighted maternal-headed households and socioeconomic status as the major sociocultural factors impacting the child participants’ language development outside of the individual factors. Furthermore, the Communicative Development Inventory revealed that 70% of adult participants were more likely to report that their child would have language skills below the 50th percentile. However, the majority (60%) of child participants’ scores on the picture-naming vocabulary task were above the 50th percentile. Adult participants also noted that their child would perform higher in semantic categories related to verbs, food, adjectives, household items, and games and routines. However, the child participants scored higher in only two of the same categories reported by their adult caregivers: household items and games and routines. Conclusion/Implications: The research study found that the Communicative Development Inventory did in fact measure what it was intended for – the expressive language skills of the Sesotho child participant. The implications for this lay in the South African Communicative Development Inventory team’s mandate to validate inventories in all South African indigenous languages. These indigenous inventories can then be used to more accurately assess indigenous speakers’ language skills which can eventually lead to the collection and development of language norms
A research report Submitted in fulfillment of the requirements for a Masters of the Arts in Speech-Language Pathology, In the Faculty of Humanities , School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Expressive Semantic Skills; esotho-Speaking Toddlers; Sesotho Picture-Naming Vocabulary Task; Sesotho Communicative Development Inventory; Language; Language Development; Indigenous Language; Communicative Development Inventory; Picture-Naming Vocabulary Task; Sesotho; South Africa; Assessment; Validation.; SDG-11: Sustainable cities and communities